Uncovering the Meaning of Hupomone for Paul: A Biblical Analysis and Its Implications for the Christian Life - Rencan Carisma Marbun (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
The aim of the research is to reveal the deep meaning of hupomone for Paul. Paul saw his obedience and loyality of the teaching he believe. He strongly defended the Jewish teaching and did the customer of his ancestors before he repented. It also happened when he lived in Christ after his repentance. This research used biblical analysis as the tool to reveal the meaning of hupomone for Paul. The result of the research indicates the hupomone for Paul is his basic attitudes, such as being stickle, stand firm, being steadfast, and being persevere as the loyal followers of best. The writer emphasizesthe meaning of hupomone is very relevant, it has impacts for Christian in this era to face many problems in the world.